Local thermometry of neutral modes on the quantum Hall edge - Venkatachalam, Vivek; Hart, Sean; Pfeiffer, Loren; West, Ken; Yacoby, Amir (Nature physics, 2012)
Electrons in two dimensions and strong magnetic fields can form an insulating two-dimensional system with conducting one-dimensional channels along the edge. Electron interactions in these edges can lead to independent transport of charge and heat, even in opposite directions. Here, we heat the outer edge of such a quantum Hall system using a quantum point contact. By placing quantum dots upstream and downstream from the heater, we measure both the chemical potential and temperature of that edge to study charge and heat transport, respectively. We find that charge is transported exclusively downstream, but heat can be transported upstream when the edge has additional structure related to fractional quantum Hall (FQH) physics. Surprisingly, this can occur even when the bulk is in an integer quantum Hall state and the edge contains no signatures of FQH charge transport. We also find an unexpected bulk contribution to heat transport at ν = 1. In most electrical conductors, heat is transported by charge carriers and so both usually flow in the same direction; but in two-dimensional electron systems subject to strong magnetic fields, certain fractional quantum Hall states can cause charge and heat to flow in opposite directions.